A brief analysis of the meaning of the doctrine of “Immaculate Conception of Virgin Mary" - QIAN, Yiting (Journal of Research for Christianity in China (JRCC), 2025)
Before the 12th century, the dogma of "the Immaculate Conception of Virgin Mary" was not explicitly confirmed, and there was no direct, clear, and rigorous evidence in the Bible to prove the validity of this doctrine. But it has been argued that this doctrine is secretly contained in the teachings of the church Fathers. In the twelfth and thirteenth centuries, this issue was extremely controversial. Well-known theologians of that time, including Thomas Aquinas, held reservations about " Immaculate Conception of Virgin Mary".